Preparation method of carbon nanotube / bamboo fungus integrated skeleton for improving heat conductivity coefficient of solid-liquid phase change material
By combining carbon nanotubes with bamboo fungus, an integrated framework is prepared and composited with solid-liquid phase change materials, the problems of uneven distribution of nanomaterials and complex processes are solved, and the thermal conductivity coefficient is improved and process simplified is achieved, which is suitable for scale Heat storage system.
Patent Information
- Application Number
- CN202411395221.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-08
AI Technical Summary
In the prior art, nanomaterials are unevenly distributed in phase change materials, resulting in insufficient formation of thermal conductivity links and complex prefabricated thermal conductivity skeleton processes, which limits the improvement of thermal conductivity and large-scale application.
By combining carbon nanotubes with bamboo fungus, an integrated framework is prepared by using a simple common carbonization method, which solves the problems of nanomaterial agglomeration and accumulation, and is compounded with solid-liquid phase change materials to improve thermal conductivity.
The stability, uniform dispersion and fixation of carbon nanotubes are achieved, and a stable thermal conductivity link and a larger effective heat exchange area are provided. The secondary agglomeration problem is overcome, and the thermal conductivity coefficient of solid-liquid phase change materials is improved. The process is simple. Suitable for large-scale applications.
Smart Images

Figure CN119286476A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of phase change heat storage, relates to the enhancement of the thermal conductivity of phase change materials, and particularly relates to a method for preparing a carbon nanotube / bamboo fungus integrated skeleton for improving the thermal conductivity of solid-liquid phase change materials. Background Art
[0002] Solid-liquid phase change materials (hereinafter referred to as "phase change materials") as a carrier for thermal energy storage are a vital part of phase change heat storage technology. Phase change materials absorb / release a large amount of heat during the phase change process, have a large heat storage density within a small temperature change range, and are expected to achieve large-scale engineering applications both technically and economically. However, the phase change materials used in heat storage technology, such as paraffin and molten salt, have low thermal conductivity, which greatly limits the charging / discharging rate of the heat storage system during operation and affects the heat storage efficiency of the heat storage system. To solve the above problems, it is necessary to improve the thermal conductivity of the phase change material so that the phase change material can adapt to the needs of actual heat storage applications.
[0003] Currently, the methods that are widely used and effective in improving the thermal conductivity of phase change materials are: (1) adding thermal conductive fillers to the phase change material and (2) introducing a thermal conductive skeleton. Method (1) uses the high thermal conductivity and geometric morphology of the thermal conductive filler to construct a thermal conductive link inside the phase change material to improve the thermal conductivity of the phase change material. It has the advantages of simple preparation process and low preparation cost. The existing technology adds a series of nanomaterials such as carbon nanotubes, graphene, silicon carbide, boron nitride, etc. as thermal conductive fillers into the phase change material. However, due to the micro-nanoscale characteristics of most nanomaterials, the van der Waals force between nanomaterials will cause the nanomaterials to attract each other and agglomerate and accumulate, resulting in uneven distribution of nanomaterials in the phase change material, local aggregation or loss, thereby affecting the formation of thermal conductive links. Method (2) prefabricates a porous skeleton with fixed heat-conducting links by physical or chemical methods and impregnates it into the phase change material to improve the thermal conductivity of the phase change material. Although it overcomes the agglomeration and accumulation problems of method (1), the process of prefabricating the skeleton usually includes more complicated process steps or involves complex chemical reaction processes, and the preparation quantity is limited. The above problems limit the large-scale application of the thermal conductive skeleton.
[0004] In addition, in order to solve the agglomeration and accumulation problems of nanomaterials, current technologies usually use dispersants, mechanical grinding, high-speed shearing and other dispersion methods to disperse nanomaterials, but the above methods cannot make the dispersed nanomaterials maintain the dispersed morphology for a long time. Especially when nanomaterials are combined with phase change materials, the surface tension of the molten liquid phase change material can easily cause the nanomaterials to re-aggregate. This phenomenon of secondary agglomeration and accumulation of nanomaterials is also one of the factors restricting the application and promotion of nanomaterials as thermal conductive fillers. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a carbon nanotube / bamboo fungus integrated skeleton for improving the thermal conductivity of solid-liquid phase change materials. The method prepares an integrated skeleton composed of carbon nanotubes carried on a porous structure of bamboo fungus through a simple co-carbonization method, thereby solving the agglomeration and accumulation problems of the carbon nanotubes themselves and the secondary agglomeration and accumulation problems that exist during application. The material selection is common, the process is simple, and the method has the potential for large-scale preparation.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a carbon nanotube / bamboo fungus integrated skeleton for improving the thermal conductivity of a solid-liquid phase change material comprises the following steps:
[0008] Step 1: dispersing carbon nanotubes in agglomerated and stacked states, and maintaining the dispersed morphology of the carbon nanotubes;
[0009] Step 2: Using bamboo fungus as a skeleton, temporarily adhering dispersed carbon nanotubes to the surface of bamboo fungus and maintaining the dispersed state to obtain a carbon nanotube / bamboo fungus impregnation precursor;
[0010] Step 3: The carbon nanotube / bamboo fungus impregnation precursor is carbonized. After carbonization, the cellulose and organic matter contained in the bamboo fungus are converted into carbon and combined with the carbon nanotubes adhered to the surface, thereby fixing the carbon nanotubes and forming a shape-stable carbon nanotube / bamboo fungus integrated skeleton.
[0011] Step 4: Compounding the carbon nanotube / bamboo fungus integrated skeleton with a solid-liquid phase change material to improve the thermal conductivity of the solid-liquid phase change material.
[0012] In one embodiment, the step 1 is to disperse the carbon nanotubes in the agglomerated and stacked state and maintain the dispersed form of the carbon nanotubes, and the implementation method is as follows:
[0013] The carbon nanotubes and the ethanol solution are uniformly mixed, and then ultrasonically dispersed for later use. Glycerol is heated at 30-60° C. and uniformly mixed with the carbon nanotube-ethanol mixed solution after ultrasonic dispersion. After mixing, heating and stirring are continued at 30-60° C. until the residual ethanol in the mixed solution is completely volatilized to obtain a carbon nanotube and glycerol mixed solution, in which the carbon nanotubes are dispersed.
[0014] In one embodiment, the step 2, using bamboo fungus as a skeleton, temporarily adhering the dispersed carbon nanotubes to the surface of the bamboo fungus and maintaining the dispersed state, is implemented as follows:
[0015] The bamboo fungus is immersed in the carbon nanotube and propylene glycol mixture to ensure that all pores of the bamboo fungus are filled with carbon nanotubes. After complete immersion, the bamboo fungus is taken out and placed in a vacuum drying oven for drying at 30-80° C. The bamboo fungus is dried to the extent that no liquid drops fall within 10-30 seconds when the immersed bamboo fungus is suspended in the air to obtain a carbon nanotube / bamboo fungus impregnation precursor.
[0016] In one embodiment, the method of ensuring that all pores of the bamboo fungus are filled with carbon nanotubes is as follows:
[0017] The viscosity of the prepared carbon nanotube and propylene glycol mixed liquid is lower than 300 mPa·s. The impregnation container is placed in a vacuum drying oven. The vacuum drying condition is 30-60° C. for 1-5 hours.
[0018] In one embodiment, the step 3, carbonizing the carbon nanotube / bamboo fungus impregnation precursor, is implemented as follows:
[0019] The dried carbon nanotube / bamboo fungus impregnation precursor is placed in a tubular furnace for heating and carbonization treatment. The carbonization conditions are uniformly heating from 20-40°C to 500-800°C, with a heating rate of 0.5-1.5°C / min, and finally keeping at 500-800°C for 1-3h, and naturally cooling to room temperature to obtain a carbon nanotube / bamboo fungus integrated skeleton.
[0020] In one embodiment, the step 4 is to compound the carbon nanotube / bamboo fungus integrated skeleton with the phase change material to improve the thermal conductivity of the phase change material, and the implementation method is as follows:
[0021] The carbon nanotube / bamboo fungus integrated skeleton is composited with a solid-liquid phase change material, the solid-liquid phase change material is used as a matrix, and the carbon nanotube / bamboo fungus integrated skeleton is used as an internal reinforcement of the matrix, and they are placed together in a vacuum drying oven. The vacuum drying conditions are 100-300° C. for 1-5 hours to obtain a composite solid-liquid phase change material with enhanced thermal conductivity.
[0022] In one embodiment, the carbon nanotubes are replaced with one or more of graphene, boron nitride, silicon nitride, gallium nitride, silicon carbide, ferroferric oxide, ferric oxide, zinc oxide and copper oxide, and the particle size of the material is 10 -2 -10 4 μm.
[0023] In one embodiment, according to the actual shape of the phase change heat storage unit in the heat storage device, the bamboo fungus is made into a spherical, ellipsoidal, cylindrical, truncated cone, rectangular parallelepiped, cube or tetrahedron shape to facilitate compounding with the solid-liquid phase change material.
[0024] In one embodiment, the solid-liquid phase change material includes organic and inorganic materials, the organic materials include: paraffin, fatty acid, polyol, lipid, and the inorganic materials include: molten salt, crystalline hydrated salt, metal.
[0025] In one embodiment, the glycerol may also be replaced by flour paste and / or syrup.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention not only overcomes the agglomeration of carbon nanotubes, but also effectively avoids the secondary agglomeration problem existing in the prior art by dispersing carbon nanotubes stably and evenly on the pore walls of bamboo fungus and then compounding them with solid-liquid phase change materials, thus providing a new method for the application of carbon nanotubes in improving the thermal conductivity of phase change materials.
[0028] 2. The present invention prepares an integrated skeleton composed of a porous structure of bamboo fungus and carbon nanotubes through a simple co-carbonization method, while providing a stable heat conduction link and a larger effective heat exchange area, which can easily improve the thermal conductivity of the solid-liquid phase change material. In addition, this method has common material selection, simple process, no pollution risks, and has the potential for large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Flow chart of the method for preparing the carbon nanotube / bamboo fungus integrated skeleton for improving the thermal conductivity of the solid-liquid phase change material of the present invention
[0030] Figure 2 This is a comparison chart of thermal conductivity of paraffin-based composite phase change materials.
[0031] Figure 3 This is a scanning electron microscope image of the surface of carbonized bamboo fungus without carbon nanotubes.
[0032] Figure 4 This is a scanning electron microscope image of the carbon nanotube / bamboo fungus integrated skeleton. DETAILED DESCRIPTION
[0033] In order to more clearly illustrate the purpose, method and advantages of the present invention, the present invention is further described in conjunction with the drawings.
[0034] like Figure 1 As shown, the present invention is a method for preparing a carbon nanotube / bamboo fungus integrated skeleton for improving the thermal conductivity of a solid-liquid phase change material, which mainly includes the following steps:
[0035] Step (1), dispersion treatment of carbon nanotubes.
[0036] Carbon nanotubes are often in a state of agglomeration and accumulation under normal conditions. In this step, the carbon nanotubes in a state of agglomeration and accumulation are mainly dispersed, and the dispersed form of the carbon nanotubes is maintained, with the aim of solving the agglomeration and accumulation problems of the carbon nanotubes themselves. Specifically, the carbon nanotubes are first mixed evenly with the ethanol solution, and then subjected to ultrasonic dispersion treatment for about 30 minutes. Then glycerol is heated to 30-60°C, and mixed evenly with the carbon nanotube-ethanol mixed solution after ultrasonic dispersion treatment, and finally the mixed substance is heated and stirred again at 30-60°C until the residual ethanol in the mixed solution is completely volatilized, at which time a mixed solution of carbon nanotubes and glycerol is obtained, in which the carbon nanotubes are in a dispersed state. For example, the temperature of both heatings can be further selected to be 40°C.
[0037] In this step, the carbon nanotubes are dispersed in glycerol by means of an ethanol solution through ultrasonic dispersion and heating stirring, and the dispersion effect is better, wherein the glycerol can maintain the dispersed form of the carbon nanotubes and provide part of the carbon, and the ethanol in the product is completely volatilized without affecting the subsequent steps.
[0038] Step (2), the carbon nanotubes are adhered to the surface of the bamboo fungus.
[0039] In this step, with bamboo fungus as the skeleton, by means of the large specific surface area of bamboo fungus, the carbon nanotubes in the dispersed state obtained in step (1) are temporarily adhered to the surface of bamboo fungus, and the dispersed state is maintained to obtain a carbon nanotube / bamboo fungus impregnation precursor, the purpose is to facilitate subsequent carbonization and finalization, and solve the secondary agglomeration and accumulation problems of carbon nanotubes. Specifically, bamboo fungus is impregnated in the carbon nanotube and propylene glycol mixed solution obtained in step (1), and it is ensured as much as possible that all pores of bamboo fungus are filled with carbon nanotubes, taken out after complete impregnation, placed in a vacuum drying oven and dried under the conditions of 30-80°C, until the bamboo fungus after impregnation is suspended and placed in the air without droplets within 10-30s, indicating that drying is complete, and a carbon nanotube / bamboo fungus impregnation precursor is obtained, and for example, it can be further selected as no droplets within 15s.
[0040] Furthermore, to ensure that all pores of bamboo fungus are filled with carbon nanotubes, the viscosity of the carbon nanotube and glycerol mixed solution prepared in step (1) of the present invention is recommended to be lower than 300 mPa·s. In addition, after the impregnation is completed, the impregnation container can be directly placed in a vacuum drying oven and vacuum dried at 30-60°C for about 1-5 hours, and the drying is generally completed. For example, the drying temperature can be selected to be 30°C.
[0041] In this step, bamboo fungus is selected as the skeleton. In addition to utilizing its large specific surface area, the more important reason is that bamboo fungus contains crude fiber, organic matter and a small amount of protein, which is conducive to maintaining the morphology of bamboo fungus and providing a part of carbon source in the later carbonization process.
[0042] Step (3), co-carbonization treatment.
[0043] In this step, the carbon nanotube / bamboo fungus impregnation precursor obtained in step (2) is carbonized to convert the cellulose and organic matter contained in the bamboo fungus into carbon and combine with the carbon nanotubes attached to its surface, thereby fixing the carbon nanotubes to form a shape-stable carbon nanotube / bamboo fungus integrated skeleton. Specifically, this step can be heated and carbonized in a tubular furnace, and the carbon nanotube / bamboo fungus impregnation precursor after drying in step (2) is placed in the tubular furnace, and the carbonization conditions are designed to be uniformly heated from 20-40°C to 500-800°C, with a heating rate of 0.5-1.5°C / min, and finally 500-800°C for 1-3h, and then naturally cooled to room temperature. The carbonization conditions are determined by the shape and size of the carbon nanotube / bamboo fungus impregnation precursor to obtain a carbon nanotube / bamboo fungus integrated skeleton.
[0044] Carbonization conditions are an important part of ensuring the stability of the shape of the carbon nanotube / bamboo fungus integrated skeleton. Under the heating conditions of the present invention, the crude fiber, organic matter and a small amount of protein in the bamboo fungus can complete the carbonization process. Under the heat preservation conditions of the present invention, the degree of graphitization of the bamboo fungus can be improved.
[0045] In this step, an integrated skeleton of a porous structure of bamboo fungus and carbon nanotubes is prepared by co-carbonization, which not only provides a stable heat conduction link, but also has a larger heat exchange area, which is conducive to compounding with solid-liquid phase change materials to improve their thermal conductivity.
[0046] Step (4), composite phase change material processing.
[0047] This step is to use the carbon nanotube / bamboo fungus integrated skeleton obtained in step (3) to composite with the solid-liquid phase change material, thereby utilizing the carbonaceous heat conduction link and large specific surface area of the carbon nanotube / bamboo fungus integrated skeleton to improve the thermal conductivity of the solid-liquid phase change material. Specifically, the solid-liquid phase change material is used as the matrix, and the carbon nanotube / bamboo fungus integrated skeleton is used as the internal reinforcement of the matrix. They are placed together in a vacuum drying oven and vacuum dried at 100-300°C for 1-5 hours to obtain a composite solid-liquid phase change material with enhanced thermal conductivity.
[0048] The vacuum drying conditions in this step are determined by the type of solid-liquid phase change material. Under the vacuum drying conditions, the solid-liquid phase change material can complete the melting process and fully fill the pores of the carbon nanotube / bamboo fungus integrated skeleton.
[0049] The invention uniformly disperses the carbon nanotubes in the pores of bamboo fungus and then compounds them with the solid-liquid phase change material, thereby perfectly overcoming the agglomeration and accumulation problems of the carbon nanotubes.
[0050] In more embodiments of the present invention, the carbon nanotubes may be replaced by one or more combinations of graphene, boron nitride, silicon nitride, gallium nitride, silicon carbide, ferroferric oxide, ferric oxide, zinc oxide and copper oxide, and the particle size of the material is ensured to be 10 -2 -10 4 μm. Among them, graphene, boron nitride, silicon nitride, gallium nitride, silicon carbide, zinc oxide and copper oxide materials have good thermal conductivity and are used to improve the thermal conductivity; ferroferric oxide and ferric oxide materials have good magnetic loss effects and can be used to improve the electromagnetic shielding performance of the material.
[0051] In more embodiments of the present invention, the glycerol mentioned above can be replaced with flour paste and / or syrup to provide a partial carbon source for the carbonization process. In more embodiments of the present invention, the bamboo fungus can be made into a spherical, ellipsoidal, cylindrical, truncated cone, cuboid, cube or tetrahedron shape according to the actual shape of the phase change heat storage unit in the heat storage device to facilitate compounding with the solid-liquid phase change material.
[0052] In more embodiments of the present invention, the solid-liquid phase change material includes organic and inorganic types, the organic type includes: paraffin, fatty acid, polyol, lipid, and the inorganic type includes: molten salt, crystalline hydrated salt, metal.
[0053] Reference again Figure 1 According to the illustrated process, the preparation of paraffin-based composite phase change material with enhanced thermal conductivity is completed. The specific process is as follows:
[0054] Step (1): uniformly mix the carbon nanotubes with a 75% ethanol solution, and then perform ultrasonic dispersion treatment for 30 minutes;
[0055] Step (2): heating glycerol at 40° C. and uniformly mixing it with the carbon nanotube-ethanol mixed solution after ultrasonic dispersion treatment in step (1); and continuously heating and stirring at 40° C. until the residual ethanol in the mixed solution is completely volatilized, thereby obtaining a carbon nanotube-glycerol mixed solution;
[0056] Step (3): the bamboo fungus is cut and separated along the axial direction, and cut into squares with a length and width of 5×5 cm respectively, and 5 pieces are overlapped in the height direction, with a total height of 1 cm. The bamboo fungus after treatment is immersed in the mixed solution of carbon nanotubes and propylene glycol described in step (2) to ensure that all pores of the bamboo fungus are filled with carbon nanotubes. After complete immersion, the bamboo fungus is taken out and placed in a vacuum drying oven at 30° C. for 2 h, and dried to the extent that no liquid drops fall when the immersed bamboo fungus is placed in the air for 15 s;
[0057] Step (4): placing the dried carbon nanotube / bamboo fungus impregnation precursor in step (3) into a tube furnace for heating and carbonization treatment, wherein the carbonization conditions are uniformly heating from 30° C. to 600° C. at a heating rate of 0.5° C. / min, and finally keeping at 600° C. for 1 hour, cooling naturally to room temperature, and then taking out;
[0058] Step (5): the carbon nanotubes / bamboo fungus after carbonization in step (4) are placed in ethanol for ultrasonic cleaning for 30 minutes to remove the carbon nanotubes not combined with the bamboo fungus, and dried at 40° C. after ultrasonic cleaning until the ethanol is completely volatilized, thereby completing the preparation of the carbon nanotube / bamboo fungus integrated skeleton.
[0059] Step (6): Compounding the carbon nanotube / bamboo fungus integrated skeleton described in step (5) with paraffin, wherein the paraffin is docosane, and the phase change temperature is 50°C. The paraffin is used as the matrix, and the carbon nanotube / bamboo fungus integrated skeleton is used as the internal reinforcement of the matrix. The two are placed together in a vacuum drying oven and taken out after 2 hours at 100°C to obtain a paraffin-based composite phase change material with enhanced thermal conductivity.
[0060] Using the same carbon nanotubes and paraffin, the carbon nanotubes are ground and dispersed according to the existing grinding and dispersion technology, and then the ground and dispersed carbon nanotubes and paraffin are mixed, and the same vacuum drying treatment as step (6) is performed to obtain a paraffin-based composite phase change material with only carbon nanotubes added.
[0061] By controlling the content of carbon nanotubes, for the above two types of paraffin-based composite phase change materials (adding carbon nanotube / bamboo fungus integrated skeleton and adding only carbon nanotubes), a series of paraffin-based composite phase change materials with carbon nanotube volume contents of 5%, 10%, 15%, 20%, 25% and 30% were prepared respectively.
[0062] The thermal conductivity of the above two types of paraffin-based composite phase change materials and pure paraffin was measured using a thermal conductivity tester. The results are as follows: Figure 2 As shown, it is obvious that the paraffin-based composite phase change material containing a carbon nanotube / bamboo fungus integrated skeleton has a higher overall thermal conductivity than the group containing only carbon nanotubes and pure paraffin.
[0063] Figure 3 This is a scanning electron microscope image of the surface of carbonized bamboo fungus without carbon nanotubes. Obviously, although the bamboo fungus has been carbonized, its pore shape is still well maintained. Figure 4 This is a scanning electron microscope image of the carbon nanotube / bamboo fungus integrated skeleton. From the image, it can be observed that the carbon nanotubes are relatively evenly attached to the pore surface of the bamboo fungus.
[0064] In summary, the present invention provides an effective new method for enhancing the thermal conductivity of solid-liquid phase change materials. The composite solid-liquid phase change material of the present invention can be used as a heat storage module for heat storage and heat exchange equipment. Due to the processability of the shape, it can be flexibly arranged in series in the form of a heat storage unit in a heat storage system, which is suitable for large-scale heat storage systems.
[0065] Although the above content has described the implementation mode of the present invention, those skilled in the art can still make changes and modifications based on the creative concept of the present invention. Therefore, the content of this specification is only an implementation mode of the present invention, and does not limit the protection scope of the patent of the present invention. Any equivalent transformation made by using the content of the present invention, or directly or indirectly applied in other related technical fields, is included in the protection scope of the present invention and should not be understood as a limitation of the present invention.
Claims
1. A method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of a solid-liquid phase change material, characterized in that: The steps include: Step 1: dispersing carbon nanotubes in agglomerated and stacked states, and maintaining the dispersed morphology of the carbon nanotubes; Step 2: Using bamboo fungus as a skeleton, temporarily adhering dispersed carbon nanotubes to the surface of bamboo fungus and maintaining the dispersed state to obtain a carbon nanotube / bamboo fungus impregnation precursor; Step 3: The carbon nanotube / bamboo fungus impregnation precursor is carbonized. After carbonization, the cellulose and organic matter contained in the bamboo fungus are converted into carbon and combined with the carbon nanotubes adhered to the surface, thereby fixing the carbon nanotubes and forming a shape-stable carbon nanotube / bamboo fungus integrated skeleton. Step 4: Compounding the carbon nanotube / bamboo fungus integrated skeleton with a solid-liquid phase change material to improve the thermal conductivity of the solid-liquid phase change material.
2. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 1, characterized in that: The step 1 is to disperse the carbon nanotubes in the agglomerated and stacked state and maintain the dispersed form of the carbon nanotubes, and the implementation method is as follows: The carbon nanotubes and the ethanol solution are uniformly mixed, and then ultrasonically dispersed for later use. Glycerol is heated at 30-60° C. and uniformly mixed with the carbon nanotube-ethanol mixed solution after ultrasonic dispersion. After mixing, heating and stirring are continued at 30-60° C. until the residual ethanol in the mixed solution is completely volatilized to obtain a carbon nanotube and glycerol mixed solution, in which the carbon nanotubes are dispersed.
3. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 1, characterized in that: The step 2, using bamboo fungus as a skeleton, temporarily adhering the dispersed carbon nanotubes to the surface of the bamboo fungus and maintaining the dispersed state, is implemented as follows: The bamboo fungus is immersed in the carbon nanotube and propylene glycol mixture to ensure that all pores of the bamboo fungus are filled with carbon nanotubes. After complete immersion, the bamboo fungus is taken out and placed in a vacuum drying oven for drying at 30-80° C. The bamboo fungus is dried to the extent that no liquid drops fall within 10-30 seconds when the immersed bamboo fungus is suspended in the air to obtain a carbon nanotube / bamboo fungus impregnation precursor.
4. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 3, characterized in that: The method for ensuring that all pores of the bamboo fungus are filled with carbon nanotubes is as follows: The viscosity of the prepared carbon nanotube and propylene glycol mixed liquid is lower than 300 mPa·s. The impregnation container is placed in a vacuum drying oven. The vacuum drying condition is 30-60° C. for 1-5 hours.
5. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 1, characterized in that: The step 3, carbonizing the carbon nanotube / bamboo fungus impregnated precursor, is implemented as follows: The dried carbon nanotube / bamboo fungus impregnation precursor is placed in a tubular furnace for heating and carbonization treatment. The carbonization conditions are uniformly heating from 20-40°C to 500-800°C, with a heating rate of 0.5-1.5°C / min, and finally keeping at 500-800°C for 1-3h, and naturally cooling to room temperature to obtain a carbon nanotube / bamboo fungus integrated skeleton.
6. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 1, characterized in that: The step 4 is to compound the carbon nanotube / bamboo fungus integrated skeleton with the phase change material to improve the thermal conductivity of the phase change material, and the implementation method is as follows: The carbon nanotube / bamboo fungus integrated skeleton is composited with a solid-liquid phase change material, the solid-liquid phase change material is used as a matrix, and the carbon nanotube / bamboo fungus integrated skeleton is used as an internal reinforcement of the matrix, and they are placed together in a vacuum drying oven. The vacuum drying conditions are 100-300° C. for 1-5 hours to obtain a composite solid-liquid phase change material with enhanced thermal conductivity.
7. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 1, characterized in that: The carbon nanotubes are replaced with one or more of graphene, boron nitride, silicon nitride, gallium nitride, silicon carbide, ferroferric oxide, ferric oxide, zinc oxide and copper oxide, and the particle size of the material is 10 -2 -10 4 μm.
8. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 1, characterized in that: According to the actual shape of the phase change heat storage unit in the heat storage device, the bamboo fungus is made into a spherical, ellipsoidal, cylindrical, truncated cone, rectangular parallelepiped, cube or tetrahedron shape to facilitate compounding with the solid-liquid phase change material.
9. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 1, characterized in that: The solid-liquid phase change materials include organic and inorganic types. The organic types include paraffin, fatty acid, polyol, lipid, and the inorganic types include molten salt, crystalline hydrated salt, and metal.
10. The method for preparing a carbon nanotube / bamboo fungus integrated framework for improving the thermal conductivity of solid-liquid phase change materials according to claim 1, characterized in that: The glycerol is replaced by flour paste and / or syrup.
Citation Information
Patent Citations
Composite phase change heat storage material using edible fungus charcoal as shaping matrix and preparation method
CN108559454A
Pleurotus eryngii-based photo-thermal conversion material and preparation method thereof
CN112898954A
Center radial carbon nanotube skeleton, composite material and preparation method and application thereof
CN116970249A
Carbon nano tube modified foamy copper-based phase change composite material as well as preparation method and application thereof
CN117844455A
Bio-based composite material as well as preparation and application thereof
CN118185583A